Exclusive Dealing - Bernheim, B. Douglas; Whinston, Michael D. (Journal of Political Economy, 1998)
In this paper, we provide a conceptual framework for understanding the phenomenon of exclusive dealing, and we explore the motivations for and effects of its use. For a broad class of models, we characterize the outcome of a contracting game in which manufacturers may employ exclusive dealing provisions in their contracts. We then apply this characterization to a sequence of specialized settings. We demonstrate that exclusionary contractual provisions may be irrelevant, anticompetitive, or efficiency‐enhancing, depending on the setting. More specifically, we exhibit the potential for anticompetitive effects in noncoincident markets (i. e., markets other than the ones in which exclusive dealing is practiced), and we explore the potential for the enhancement of efficiency in a setting in which common representation gives rise to incentive conflicts. In each instance, we describe the manner in which equilibrium outcomes would be altered by a ban on exclusive dealing. We demonstrate that a ban may have surprisingly subtle and unintended effects.